Depth and Perspective Perception of Flat Images in Static and Dynamic Visual Scenes - Fazlyyyakhmatov, Marsel; Nurieva, Yana; Khafizov, Ildar; Zhegallo, Alexander; Antipov, Vladimir (International Journal of Criminology and Sociology, 2022)
The paper shows that a sense of depth can arise from two-dimensional (2D) scenes without the presence of a stereoscopic depth signal. Experimental information was obtained on three-dimensional (3D) visual perception of 2D static and dynamic scenes. The technique is based on fixing the conditions of eye movement during the perception of two-dimensional stimulus scenes. To obtain registration of the depth perception effects, they used volume and spatial perspective of 2D images (3D phenomenon), and a binocular eye tracker. The 3D phenomenon is identified using 3D raster images. It is assumed that the comparison of eye movements during a 3D raster image viewing allows you to identify uniquely the effects of the 3D phenomenon of stimulus planar scenes displayed on the monitor screen. The first part of the work shows the conditions for the emergence of a 3D phenomenon on two plots of dynamic and static scenes. The second part demonstrates the three-dimensional attributes of dynamic scenes with the highlighting of various video components. We emphasize that dynamic and static scenes are obtained directly from TV programs. The proposed graphical and mathematical method of analysis made it possible to show qualitatively the perception of the 3D phenomenon by KFU students and revealed the features of volume observation for planar images without the occurrence of binocular disparity.